Republic of Estonia : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2011)
The staff report for the 2011 Article IV Consultation concluded that a vibrant recovery marked Estonia's first year in the euro area, albeit amid nascent tensions. The economy's strong rebound has been grounded in a proven track record of prudent macroeconomic policies. Executive Directors endorsed that Estonia faces an increasingly challenging environment as it looks to continue implementing policies preserving macroeconomic policy credibility and safeguarding sustainable growth. They also stated that, for the financial sector, the challenge entails safeguarding stability in the context of heightened global financial tension.